Influence of suturing material on wound healing – An experimental study on dogs - Gazivoda, Dragan; Pelemiš, Dejan; Vujašković, Goran; Djurdjević, Slaviša (Vojnosanitetski pregled, 2015)
Background/Aim. The most common materials implanted in the human organism are suture materials that are classified on the basis of several criteria, usually the origin, structure, and properties. The properties of suture materials are related to its absorbability and non-absorbability. When using resorbable materials it is of great importance to determine whether its absorbability and tensile strength help wound healing in function of time. Sutures themselves can become a source of inflammation, that may reduce or compromise the potential of reparation and regeneration. The aim of this experimental study on dogs was to ascertain whether the absorption rate and the degree of local tissue reactions differ from information provided by the manufacturers, whether there are differences between the applied suture materials and which of the used suture materials have better effect on wound healing. Methods. Experimental testing of the selected suture materials basic characteristics was performed on 6 German Shepherd dogs, which, after induction of general anesthesia, were made 3 identical incisions each in all 4 quadrants (left and right side of the upper and lower jaws), so that 12 horizontal incisions were formed, 10 mm long, 20–25 mm distant from one another, on each animal. Randomly, incisions were stitched up in the following order, starting from back to front: catgut, Dexon®, Vicryl-Rapid®. The experiment was terminated by histopathological examination of tissue samples, taken on postoperative day 3, 7, 14 and 21 in order to identify the effect of healing and the degree of local reaction. Results. The obtained results suggest that catgut has the highest absorption rate, while Dexon® the lowest. Vicryl-Rapid® causes the lowest level of local reactions, while Dexon® the highest. Conclusion. There is no ideal suture material because various patient factors also influence the wound healing process.